Does rising land price promote the circulation industry development? An analysis of internet-based moderating effects - Yuanyuan Yin; Zhang Liu; Chen Gao (Heliyon)
With the rapid development of the Internet, digital technology is increasingly integrating into the modern circulation system. The influence mechanisms of land prices on the development of the circulation industry are gradually transforming. Using data from 104 major cities in China from 2003 to 2021, this study uses the panel two-way fixed effects model, moderating effects model and threshold regression method to examine the mechanisms by which land prices affect the circulation industry development and the moderating role of Internet development. The results show that elevated land prices significantly stimulate the growth of the circulation industry, leading to an expansion in the circulation industry scale, optimization of its structure, and enhancement of its facilities. The findings remain robust even after addressing endogeneity concerns and conducting various robustness tests. Moreover, the impact of high land prices on the circulation industry is more pronounced in small and medium-sized cities group as well as central region cities group. Real estate investment and industrial structure upgrading are the key channels through which high land prices promote the development of the circulation industry. Additionally, Internet development has a positive moderating effect on the promotion that high land prices stimulate the development of the circulation industry. Notably, only when Internet development surpasses a certain threshold that the promotional effect of land prices on the circulation industry development be fully realized. Based on the above conclusions, the government should continue to deepen the market-oriented reform of land elements, implement precise industrial policy support for the circulation industry and promote circulation digital transformation.